Liberal dimensions of European integration: Guy Verhofstadt’s concept (Economic and Political Thought, 2015)
The article discusses a new vision of European integration formulatedby Guy Verhofstadt, a charismatic and uncompromising leader of Europeanliberals. The vision is based on six points that require re-evaluation: newfederalism and democratization of the Union, a reform of the Europeanfinances, environmental policy, European alter-globalism, the EuropeanUnion security policy and the military of the European Union, and foreignpolicy. Liberals, despite political difficulties and a failure in the last Europeanelections are still a major force in the European Parliament. ALDE is ableto create a fresh concept of integration tailored to the dynamic changes onthe continent.